2014
DOI: 10.3738/1982.2278.975
|View full text |Cite
|
Sign up to set email alerts
|

ATTRACTIVE FOOD IN MONITORING OF POPULATION Fruit flies (Diptera: Tephritidae) on guava orchard

Abstract: RESUMO:Os objetivos desta pesquisa foram avaliar a eficiência de atrativos alimentares no monitoramento de moscas das frutas e estudar a flutuação populacional destes tefritídios correlacionada com os elementos meteorológicos, em pomar de goiaba localizado no município de Jaboticabal, SP. Como atrativos alimentares foram utilizados: a) proteína hidrolisada de milho (Moscatex ) a 5% mais suco açucarado de goiaba a 50%. Foram instaladas cinco armadilhas para cada tratamento, que foram substituídas a cada 15 dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Rodríguez et al (2015) found that Cera Trap ® associated with inexpensive traps made of transparent bottles were effective in the control of A. serpentina Wiedemann (Diptera: Tephritidae). However, Duarte et al (2013) used Moscatex ® lure (pure or mixed with guava juice) and found that McPhail trap was more efficient than the weak fly trap in the capture of Anastrepha spp. and C capitata.…”
Section: Resultsmentioning
confidence: 99%
“…Rodríguez et al (2015) found that Cera Trap ® associated with inexpensive traps made of transparent bottles were effective in the control of A. serpentina Wiedemann (Diptera: Tephritidae). However, Duarte et al (2013) used Moscatex ® lure (pure or mixed with guava juice) and found that McPhail trap was more efficient than the weak fly trap in the capture of Anastrepha spp. and C capitata.…”
Section: Resultsmentioning
confidence: 99%